RECONSTRUCTION OF THE HISTORY OF HAMZAH FANSURI’S LIFE AND RECOGNITION OF HIS WORKS - Miswari Miswari (Sekolah Tinggi Agama Islam Sadra, 2023)
Hamzah Fansuri is an important figure in the history of Islam in Indonesia. He is an important figure who is always discussed within the framework of discussing the dynamics of the development of Islam and Sufism in the archipelago. The purpose of this article is to trace the life history of Hamzah Fansuri. Many researchers have not studied the comprehensive history of Hamzah Fansuri’s life. Researching the life history and basic teachings of a Sufi is very important to understand the biographical background of the development of his teachings and to know the principles of the teachings, through his works. There are two important ways to understand the basic teachings of a Sufi. This article, first, examines general considerations and presents a new construction of Hamzah Fansuri’s intellectual life and career and, second, browse the main teachings of Hamzah Fansuri through his works, using an analytical-descriptive-critical method. This qualitative research uses library research. Data collection was taken from various references from the biography of Hamzah Fansuri. According to the findings of this article, Hamzah Fansuri was born in Samudra Pasai, studied in Singkil, and then traveled to the Middle East via Barus. Returning to the archipelago, he made a career in Ujong Pancu, Aceh Besar. Hamzah Fansuri died in Mecca in 1527 AD. Throughout his career, Hamzah Fansuri wrote approximately thirty poems and three works of prose, namely Sharāb al-‘Āshīqīn which describes the process of the spiritual journey, Asrār al-‘Ārifīn which describes the philosophical teachings of Sufism, and al-Muntahī which explains the meaning of Sufi expressions.